ALOKASI BELANJA MODAL KABUPATEN DAN KOTA DITINJAU DARI INDIKATOR KINERJA KEUANGAN DAERAH - Yunus Harjito; Yunia Ike Lestari; Faiz Rahman Siddiq (Jurnal Bisnis dan Kewirausahaan, 2020)
This study aims to analyze the capital expenditure allocation of district and municipal as seen from local financial performance indicators. The data in this study is secondary data obtained from regional financial reports that have been audited by BPK RI. The variables that are expected to influence the allocation of capital expenditure in this study are the Regional Financial Independence, locally-generated revenue Effectiveness, Financial Efficiency, Debt Service Coverage Ratio, and Harmony of Expenditure. The sample in this study using districts and cities in East Java Province and selected based on purposive sampling method with five years observation period and using data analysis method used is multiple linear regression. The results showed that there are three influential variables: Regional Financial Independence, Local Financial Efficiency, and Harmony of Expenditure, while the other two variables namely locally-generated revenue Effectiveness and Debt Service Coverage Ratio have no effect on capital expenditure allocation.